Adherence to statins and the risk of psoriasis: a population‐based cohort study. (12th June 2015) - Chodick, G.; Weitzman, D.; Shalev, V.; Weil, C.; Amital, H.
Summary Background Statins have been shown to downregulate immune mechanisms activated in psoriasis. However, previous studies on their potential role in preventing psoriasis have yielded conflicting results. Objectives To assess the relationship between adherence to statins and the risk of psoriasis. Methods This retrospective cohort study included 205 820 health plan enrollees in Israel (mean age 55 years; 54·1% women) who initiated statin treatment from January 1998 through to September 2009. Adherence to statins, measured by the proportion of days covered (PDC), throughout the entire follow‐up period (mean 6·2 years) was recorded. Diagnosis codes of psoriasis were assigned by a dermatologist or rheumatologist, or at discharge from hospital. Results During 1·28 million person‐years (PY) of follow‐up (median 5·74 years per person; interquartile range 3·78–8·36), 5615 cases of psoriasis (incidence density rate 4·4 per 1000 PY) were recorded. Compared with patients who did not adhere to statins (PDC < 20%), patients covered by statins for 40–59% of the time had a significantly lower risk of psoriasis (P < 0·05), with hazard ratios (HRs) of 0·84 and 0·74 among men and women, respectively. Among patients who adhered better to statins (PDC ≥ 80%), HRs were 0·88 (95% CI 0·79–0·98) and 1·00 (95% CI 0·90–1·11) among men and women, respectively. Conclusions The results of the current study suggest that high and long‐term adherence to statins is not associated with a meaningful reduction in the risk of developing psoriasis.